Heterologous vaccination with inactivated vaccine and mRNA vaccine augments antibodies against both spike and nucleocapsid proteins of SARS-CoV-2: a local study in Macao - Ng, Hoi Man; Lei, Chon Lok; Fu, Siyi; Li, Enqin; Leong, Sek In; Nip, Chu Iong; Choi, Nga Man; Lai, Kai Seng; Tang, Xi Jun; Lei, Chon Leng; Xu, Ren-He (Frontiers in Immunology, 2023)
The mRNA vaccines (RVs) can reduce the severity and mortality of severe acute respiratory syndrome coronavirus (SARS-CoV-2). However, almost only the inactivated vaccines (IVs) but no RVs had been used in mainland China until most recently, and the relaxing of its anti-pandemic strategies in December 2022 increased concerns about new outbreaks. In comparison, many of the citizens in Macao Special Administrative Region of China received three doses of IV (3IV) or RV (3RV), or 2 doses of IV plus one booster of RV (2IV+1RV). By the end of 2022, we recruited 147 participants with various vaccinations in Macao and detected antibodies (Abs) against the spike (S) protein and nucleocapsid (N) protein of the virus as well as neutralizing antibodies (NAb) in their serum. We observed that the level of anti-S Ab or NAb was similarly high with both 3RV and 2IV+1RV but lower with 3IV. In contrast, the level of anti-N Ab was the highest with 3IV like that in convalescents, intermediate with 2IV+1RV, and the lowest with 3RV. Whereas no significant differences in the basal levels of cytokines related to T-cell activation were observed among the various vaccination groups before and after the boosters. No vaccinees reported severe adverse events. Since Macao took one of the most stringent non-pharmaceutical interventions in the world, this study possesses much higher confidence in the vaccination results than many other studies from highly infected regions. Our findings suggest that the heterologous vaccination 2IV+1RV outperforms the homologous vaccinations 3IV and 3RV as it induces not only anti-S Ab (to the level as with 3RV) but also anti-N antibodies (via the IV). It combines the advantages of both RV (to block the viral entry) and IV (to also intervene the subsequent pathological processes such as intracellular viral replication and interference with the signal transduction and hence the biological functions of host cells).